CHITIN OLIGOMERS PRODUCTION FROM FUNGAL MYCELIUM CULTIVATING ON CASSAVA STARCH MEDIUM - Krairak*, Somchai; Arttisong, Duenpen (CURRENT APPLIED SCIENCE AND TECHNOLOGY, 2007)
The morphologies and growths of Monascus sp. KB20M1, Mucor rouxii and Rhizopus oligosporus were studied on MYS medium containing cassava starch as a C-source and the maximum dry mycelium weights were produced by the condition of 250 rpm of rotary shaker at 30oC for 7 days, which gave the yields of 11.24, 8.08 and 8.15 g/l, respectively. The analysis of FT-IR spectrophotometer on fungal mycelium of the three-species showed the composition of chitin-chitosan by the detection of amide I group (1640-1660 cm.-1) and hydroxyl group (2920- 2930 cm.-1). The chitin oligomers production was performed on fungal mycelium hydrolysis by biological method (chitinase) and chemical method (phosphoric acid). The retrieved product of chitin oligomers were varied due to the hydrolysis conditions and time-period. The O1 and O2 samples from enzymatic digestion and O3 sample from the chemical digestion were selected for further study of biological activity on Phalaenopsis growth. It was found that chitin oligomers enhanced the survival and rooting of Phalaenopsis. Phalaenopsis which was immersed in the O2 sample at the concentration of 1000-time dilution for 3 hr presented the maximal growth (p<0.01). The survival and rooting was found at 100% and the average length of rooting was about 94.00 mm. Keywords: chitin oligomers, chitooligomers, fungal mycelium, Phalaenopsis Corresponding author: E-mail: kksomcha@kmitl.ac.th